SUPER STRUCTURE OF VERNADITE IN CO-RICH MANGANESE CRUSTS FROM THE MIDDLE PACIFIC SEAMOUNTS - Ye Y.; Han J.; Wu D.; Chen X.; Shen Z.; Wang B. (My University, 2007)
Co-rich manganese crusts from the Middle Pacific Seamounts are composed mainly of vernadite which is in short of (001) and (002) basal spacing, for the reason that in its crystal structure there are two sorts of octahedral sheets, i. e., triclinic and hexagonal sheets, stacking together along c axis without ordering. Super structure defraction in low-angle area with a d value >2.0 nm is found in some samples. This is quite possibly related with certain kind of long-range ordering in vernadite, indicating periodical or regular arrangement of sheets with different symmetry. For the samples without super structure defraction, the peak appears after being heated in 110°C for 12 h. While heated in air, Mn (III) in triclinic sheet could be oxidized into Mn (IV). This may change the symmetry of the sheet and then the ordering of vernadite. It is believed that the super structure of vernadite is an indicator of its formation environment.
Keywords: CO-RICH CRUSTS; MIDDLE PACIFIC SEAMOUNTS; PHASE TRANSFORMATION; SUPER STRUCTURE